Climate Change Education through Earth Observation: An Approach for EO Newcomers in Schools - Asimakopoulou, Panagiota; Nastos, Panagiotis; Vassilakis, Emmanuel; Assimina Antonarakou; Hatzaki, Maria; Katsigianni, Ourania; Papamatthaiou, Maria; Kontoes, Charalampos (Sustainability, 2023)
Earth Observation (EO) is widely recognized as a powerful tool for Climate Change and Sustainability Education (CCSE); however, the uptake of EO data in schools is still limited due to technical, motivational, or informational barriers. A major factor for the exploitation of EO in schools is the availability of curriculum-relevant pedagogical content that is attractive and personally meaningful to learners. Here, we examine whether an EO-based learning scenario developed for primary schools and implemented by EO novice teachers and students, based solely on written instructions, can serve as an effective entry point for incorporating EO into schools and addressing CCSE objectives. Our study showed that: (a) cloud-based EO tools are suitable for EO-novice teachers and students, who quickly become familiar with them and grasp basic EO concepts; (b) the combined use of EO-based and place-based learning helps students bridge the local and the global perspective of Climate Change (CC) impacts; (c) EO-based educational material stimulates students’ interest for satellites and EO technology; (d) the phenomenon-based approach grabs students’ attention, provokes their curiosity, and acts as a springboard for scientific inquiry on CC impacts; and (e) our scenario’s learning approaches promoted teachers’ upskilling and intra-school collaboration.